TEZAURUS TUSHUNCHASI VA ILMIY YONDASHUV («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In this article, the concept of “thesaurus”, its origin and different views on learning are revealed based on scientific approaches. Opinions are expressed about how important the thesaurus is in every aspect of life, in every field.
Keywords: thesaurus, indexing, hierarchical, adequate, associative, synonymous, anaphoristic, elliptical, convolution.